Institutional hypertension control in rural Malaysia: A single center study - Mohd Shah, Azarisman Shah; Ngow, Harris Abdullah; O, Marzuki; A.M., Puteri Melor; Ab Rahman, Jamalludin; Mohamed, Sahimi; Satwi, Sapari; S, Noorfaizan; Maskon, Oteh (Wolters Kluwer, 2008)
Objectives: Hypertension is one of the most important risk factors for Cardiovascular Disease in Malaysia. Population-based hypertension control is extremely poor at only 6% based on the 1996 National Health and Morbidity Survey. It is important to gauge the level of hypertension control in institutional follow-up as it has important ramifications on the delivery of service amongst healthcare professionals in Malaysia. Methods: Three hundred and thirty one consecutive patients presenting with hypertension to the Medical Outpatients clinic of Hospital Tengku Ampuan Afzan, Kuantan, Malaysia were enrolled into a prospective observational study. Blood pressure readings were taken with manual sphygmomanometers. A review of the medications and co-morbidities was then undertaken. Results: The majority of patients were male 64.65%, with a mean age of 60.1±11.0 years. The mean systolic blood pressure (SBP) was 139.3±21.0 mmHg and the diastolic blood pressure (DBP) was 81.6±10.4 mmHg. 64.9% of patients had blood pressures (BP) within the 140/90 mmHg target. The mean blood pressure in this group was 127.1±11.5/77.8±7.7 mmHg. The majority of patients were on either 2 (46.5%) or 3 (25.9%) anti-hypertensives. Females had a significantly higher SBP 144.0±22.5 vs 136.8±19.7 mmHg (p=0.004, Independent t test). SBP was also found to be mildly correlated with gender (r = 0.16, p = 0.003), age (r = 0.11, p = 0.04) and hyperlipidaemia (r = 0.10, p = 0.05). Conclusion: The level of hypertension control is certainly equivalent if not better than western centers. It proves that the level hypertension control in tertiary institutions is far superior to that of population-based centers. This could be attributed to the availability of both a highly trained staff, greater surveillance and better medications.